2019
DOI: 10.1007/s13205-019-1711-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity guided isolation of antidiabetic and antioxidant compound from Xylocarpus granatum J. Koenig bark

Abstract: The present study was designed to identify antidiabetic and antioxidant constituents from ethanol bark extract of a medicinally important mangrove plant Xylocarpus granatum J. Koenig, using in vitro bioactivity-guided fractionation. The repeated fractionation of X. granatum ethanol bark extract (XGEB) by silica gel column chromatography yielded a compound with strong antidiabetic and antioxidant potential. The bioactive compounds likely to be present in the XGEB fraction were identified by FT-IR, 1 H & 13 C NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Zamani et al (2015) reported plant antioxidant activity of X. granatum seed kernel with IC50 10.61 μg/ml. Similarly, in vitro antioxidant activity has been reported by Das et al (2019). The antioxidant potential of X. granatum revealed in this study is in close agreement with both above mentioned reports.…”
Section: Discussionsupporting
confidence: 93%
“…Zamani et al (2015) reported plant antioxidant activity of X. granatum seed kernel with IC50 10.61 μg/ml. Similarly, in vitro antioxidant activity has been reported by Das et al (2019). The antioxidant potential of X. granatum revealed in this study is in close agreement with both above mentioned reports.…”
Section: Discussionsupporting
confidence: 93%
“…In folklore, the X. granatum plant has been applied to treat malaria, fever, cholera, dysentery, and diarrhea in many countries including India. The extraction of leaves, fruits, and barks of X. granatum possesses potential free radical scavenging activities [ 4 ]. Besides, Uddin et al [ 16 ] proposed that this plant extract chemicals have a variety of medicinal properties and in Bangladesh, and it was employed for the treatment of fever, malaria, cholera, diarrhea, and dysentery.…”
Section: Resultsmentioning
confidence: 99%
“…The isolated compounds from the X. granatum have antidiabetic activity. Xylogranin B, xyloccensin I, and xyloccensin S [ 70 ] exhibited antidiabetic activity by inhibiting α -amylase, α -glucosidase, and protein tyrosine phosphatase 1B (PTP1B), respectively [ 4 , 52 ]. Xylogranin B acts with the concentration of the IC 50 48.9 nM or inhibited TCF/ β -catenin transcriptional activity with IC 50 values of 270 and 330 nM [ 4 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Togean Central Sulawesi, X. granatum seeds have activity inhibition of tyrosinase and antioxidants which has the potential to brighten the skin (Zamani et al 2015). Das et al (2019) reported that leaves, fruits, and barks of X. granatum can be processed into medicine for various diseases e.g. : fever, malaria, cholera, dysentery, thrush, and diarrhea.…”
Section: Mangrove Densitymentioning
confidence: 99%